Torsion of the appendix testis in undescended testes as a rare cause of groin swelling - Daniel Pasquale Cinelli; Fadi Atwan; Anne G. Carroll; Salvatore Cascio (Elsevier, 2021)
A 10 year-old boy presented to the emergency department with torsion of an Appendix Testis in an undescended testis. The diagnosis was suspected clinically and confirmed by ultrasound imaging. Intra-operatively, the testis was well perfused. A black, necrotic pedunculated Appendix Testis was present, excised and an orchidopexy performed. It is likely that torsion of an Appendix Testis in undescended testes is under-reported. With this case report, we wish to highlight torsion of Appendix Testis as a relevant differential diagnosis in patients presenting with groin swelling and undescended testis.